A randomized trial of an acceptance‐based behavioral intervention for weight loss in people with high internal disinhibition. Issue 12 (2nd November 2016) - Lillis, Jason; Niemeier, Heather M.; Thomas, J. Graham; Unick, Jessica; Ross, Kathryn M.; Leahey, Tricia M.; Kendra, Kathleen E.; Dorfman, Leah; Wing, Rena R.
Abstract : Objective: To determine whether an acceptance‐based behavioral intervention (ABBI) produces better weight losses than standard behavioral treatment (SBT) among individuals reporting high internal disinhibition. Methods: Participants were 162 adults with overweight or obesity (mean BMI 37.6 kg/m 2 ) randomly assigned to ABBI or SBT. Both interventions provided the same calorie intake target, exercise goal, and self‐monitoring skills training. SBT incorporated current best practice interventions for addressing problematic thoughts and emotions. ABBI utilized acceptance‐based techniques based on Acceptance and Commitment Therapy. ABBI and SBT were compared on weight change and internal disinhibition change over 24 months. Results: Mixed models analysis showed mean weight loss at 24 months was −4.1% (SE = 0.88) for ABBI and −2.4% (SE = 0.87) for SBT ( P = 0.204). Secondary analyses showed that the ABBI group regained less weight from the end of treatment to the final follow‐up (4.6 vs. 7.1 kg; P = 0.005), and that a significantly higher proportion of ABBI participants achieved a 5% weight loss (38% vs. 25%; P = 0.038) at 24 months. Conclusions: Results suggest that ABBI could be helpful for improving the maintenance of weight loss for individuals who report high internal disinhibition.